(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The aim of this study is to determine how riders and traffic police assess the accidents in Batasan Hills. Motorcycles are the most numerous vehicles in the Philippines, so it is inevitable that motorcycles also have the most number of accidents. The researcher conducted this study to raise awareness of the possible causes and effects of a motorcycle accident. What is the response of the traffic police whenever there is an accident, and what is the condition of the accident victims? The majority of motorcycle riders did not have a legal driver’s license and would prefer to avoid the police. Head injuries, fractures, lacerations, and contusions were the most common motorcycle injuries. The majority of the incidents were caused by an unfinished construction road. Motorcycle accidents can be reduced through increased law enforcement, public education, the usage of helmets, and good condition of construction roads. According to the twenty-five respondents, motorcycle riders assess the accidents in Batasan in terms of roadways as Unfinished Construction roads. In terms of the drivers, the Destruction of drivers on the road is the main cause of accidents. And in terms of weather conditions, the respondents said sudden use of brakes when it’s raining causes skidding on the road, which is a cause of accidents. According to the respondents, unfinished construction roads are the common reason that can cause accidents. Because most of the motorcycle riders didn’t notice the wrecked road while driving are on the road. In terms of drivers, intoxicated drivers are the most common cause of accidents. In Addition, sudden use of brakes when it’s raining causes skidding on the road.